2004
DOI: 10.1093/jac/dkh470
|View full text |Cite
|
Sign up to set email alerts
|

Pitfalls of polymyxin antimicrobial susceptibility testing of Pseudomonas aeruginosa isolated from cystic fibrosis patients

Abstract: Polymyxin resistance among common CF pathogens is not rare, thus underlining the necessity of accurate susceptibility testing. When compared with the agar dilution method, it was found that the microdilution method is a valid, rapid and cost effective alternative for the determination of polymyxin activity. The performance of the microdilution method was most reliable after prolonged incubation (48 h) at a susceptibility breakpoint of < or =4 mg/L according to the BSAC guidelines (specificity 91%, sensitivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
40
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 8 publications
6
40
0
1
Order By: Relevance
“…In contrast, only 15% of laboratories use AD or BMD for testing colistin. Numerous studies have demonstrated very good agreement between AD and BMD (4,6,20,21), with the exception of P. aeruginosa isolated from cystic fibrosis patients, in whom AD might have more readily detected colistin resistance (5,6). Among the 6 methods used in our study, we found the greatest EA between TDS (83%) and BMD-T, and between AD (80%) and BMD-T ( Table 2).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…In contrast, only 15% of laboratories use AD or BMD for testing colistin. Numerous studies have demonstrated very good agreement between AD and BMD (4,6,20,21), with the exception of P. aeruginosa isolated from cystic fibrosis patients, in whom AD might have more readily detected colistin resistance (5,6). Among the 6 methods used in our study, we found the greatest EA between TDS (83%) and BMD-T, and between AD (80%) and BMD-T ( Table 2).…”
Section: Discussionsupporting
confidence: 59%
“…More recent data suggest that this is also true for contemporary Pseudomonas aeruginosa isolates. Up to 32% of VMEs have been observed by DD testing compared to reference MICs obtained using either broth or agar dilution reference methods (4)(5)(6)(7)(8). The Clinical and Laboratory Standards Institute (CLSI) provides DD breakpoints for P. aeruginosa (9) but not for any other GNB, and one manufacturer of colistin disks (BBL, BD Diagnostic Systems, Sparks, MD) suggests that any DD zone in the susceptible range be confirmed by a method that yields an MIC (Sensi-Disc antimicrobial susceptibility test disc package insert, no.…”
mentioning
confidence: 99%
“…Several studies have shown nearly complete agreement in the susceptibility results for polymyxin B and those for colistin, particularly when colistin sulfate was used (41,49,55,130,153,179). In one report, the MICs of colistin were slightly higher than those of polymyxin B using agar dilution, although the categorical agreement was very good when the 4-g/ml breakpoint was used (73). Taken together, the data suggest that susceptibility to one agent should nearly always imply susceptibility to the other.…”
Section: Susceptibility Testing Methodologymentioning
confidence: 98%
“…Several recent studies compared these two methods (15,55,73,111). Although MICs tended to be slightly higher using agar dilution, in general, a very good correlation between the two methods was seen using CLSI methodology (15,55,111).…”
Section: Susceptibility Testing Methodologymentioning
confidence: 99%
See 1 more Smart Citation